198k views
4 votes
Solve x2 + 6x + 7 = 0. (2 points)

2 Answers

5 votes

Answer:


x=-3+√(2)\text{ and }x=-3-√(2)

Explanation:

Given quadratic equation,


x^2 + 6x + 7 = 0

By quadratic formula,


x=(-6\pm √(6^2-4* 1* 7))/(2* )


=(-6\pm √(36-28))/(2)


=(-6\pm √(8))/(2)


=(-6\pm 2√(2))/(2)


=-3\pm √(2)


\implies x=-3+√(2)\text{ or }x=-3-√(2)

Hence, the solution of the given equation are,


x=-3+√(2)\text{ and }x=-3-√(2)

User Robb Vandaveer
by
5.7k points
5 votes

Answer:


x=-3-√(2) or
x=-3+√(2)

Explanation:

The given equation is


x^2+6x+7=0

Comparing to
ax^2+bx+c=0, we have a=1,b=6,d=7

The solution to this equation can be obtained using the quadratic formula;


x=(-b\pm √(b^2-4ac) )/(2a)

Plug in the values to get;


x=(-6\pm √(6^2-4(1)(7)) )/(2(1))


x=(-6\pm √(36-28) )/(2)


x=(-6\pm √(8) )/(2)


x=(-6\pm 2√(2) )/(2)


x=-3-√(2) or
x=-3+√(2)

User Tooluser
by
6.0k points